2016
DOI: 10.1095/biolreprod.116.138370
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Toxicant Exposure Is Associated with Transgenerational Adenomyosis in a Murine Model

Abstract: The common environmental toxicant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD or, commonly, dioxin) is a known endocrine disruptor that has been linked to the development of endometriosis in experimental models. Using a murine model, we previously demonstrated that in utero TCDD exposure promotes the transgenerational development of an “endometriosis-like” uterine phenotype consisting of reduced responsiveness to progesterone, as well as subfertility and an increased risk of preterm birth. Because adenomyosis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
(83 reference statements)
2
28
0
Order By: Relevance
“…Adenomyosis, like endometriosis, has been associated with reduced fertility, pelvic pain, heavy menstrual bleeding and dysmenorrhea [5, 101]. The causes of adenomyosis are currently unknown, although both human and animal studies have suggested a role of inflammatory processes in the development of this disease [102105]. In our murine model, we recently reported the transgenerational occurrence of adenomyosis in mice exhibiting the endometriosis-like uterine phenotype as a consequence of developmental TCDD exposure of F1 animals [102].…”
Section: Transgenerational Reproductive Dysfunction In a Mouse Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Adenomyosis, like endometriosis, has been associated with reduced fertility, pelvic pain, heavy menstrual bleeding and dysmenorrhea [5, 101]. The causes of adenomyosis are currently unknown, although both human and animal studies have suggested a role of inflammatory processes in the development of this disease [102105]. In our murine model, we recently reported the transgenerational occurrence of adenomyosis in mice exhibiting the endometriosis-like uterine phenotype as a consequence of developmental TCDD exposure of F1 animals [102].…”
Section: Transgenerational Reproductive Dysfunction In a Mouse Modelmentioning
confidence: 99%
“…The causes of adenomyosis are currently unknown, although both human and animal studies have suggested a role of inflammatory processes in the development of this disease [102105]. In our murine model, we recently reported the transgenerational occurrence of adenomyosis in mice exhibiting the endometriosis-like uterine phenotype as a consequence of developmental TCDD exposure of F1 animals [102]. Within this recent study, we conducted a retrospective analysis of uteri from TCDD exposed F1 female mice and two generations of their offspring to determine whether histological evidence of adenomyosis was present.…”
Section: Transgenerational Reproductive Dysfunction In a Mouse Modelmentioning
confidence: 99%
See 3 more Smart Citations